2018
DOI: 10.1177/1071100717745501
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Vitamin D Deficiency in Patients With Talar Osteochondral Lesions

Abstract: Level III, comparative study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…14 A high rate of vitamin D deficiency or hypovitaminosis D was also identified in patients with OLT and juvenile osteochondritis dissecans. 21,27 Vitamin D deficiency is potentially an important cofactor in the multifactorial development of osteochondritis dissecans. 27 Adolescent participants often have vitamin D insufficiency, and serum vitamin D levels below 20 ng/mL were observed in 64.8% of adolescent girls and 52.1% of adolescent boys.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 A high rate of vitamin D deficiency or hypovitaminosis D was also identified in patients with OLT and juvenile osteochondritis dissecans. 21,27 Vitamin D deficiency is potentially an important cofactor in the multifactorial development of osteochondritis dissecans. 27 Adolescent participants often have vitamin D insufficiency, and serum vitamin D levels below 20 ng/mL were observed in 64.8% of adolescent girls and 52.1% of adolescent boys.…”
Section: Discussionmentioning
confidence: 99%
“…21,27 Vitamin D deficiency is potentially an important cofactor in the multifactorial development of osteochondritis dissecans. 27 Adolescent participants often have vitamin D insufficiency, and serum vitamin D levels below 20 ng/mL were observed in 64.8% of adolescent girls and 52.1% of adolescent boys. 2 Although serum vitamin D level was not measured in this study, they might have had vitamin D insufficiency because the subjects were juvenile OLT patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in situations where the underlying bony architecture is further weakened, such as occurs with decreased bone mineral density, the risk for mechanical failure is even higher. 33 Consequently, altered bony microarchitecture due to vitamin D deficiency might lead to more severe OCD of the talus. For this reason, we further analyzed the cohort for a possible correlation between vitamin D levels and the degree of OCD as analyzed in MR imaging.…”
Section: Discussionmentioning
confidence: 99%
“…20,23,30 Moreover, we and others have shown that vitamin D deficiency also affects patients with foot and ankle disorders. 1,16,32,33 Further, it has been suggested that hypo-vitaminosis D is related to the onset of OCD. 25,33 However, data on the vitamin D status of patients with OCD are scarce and to date mostly limited to measurements in adolescents.…”
mentioning
confidence: 99%
See 1 more Smart Citation